The Social Media President Barack Obama and the Politics of Digital Engagement - Katz, James E.; Barris, Michael; Jain, Anshul; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
The proliferation of social media has altered the way that people interact with each other - leveling the channels of communication to allow an individual to be'friends' with a sitting president. In a world where a citizen can message Barack Obama directly, this book addresses the new channels of communication in politics, and what they offer.
Keywords: Science; Science; Science, general